Endothelial NO-Synthase Gene-Enhanced Progenitor Cell Therapy for Pulmonary Arterial Hypertension. Issue 7 (11th September 2015) - Granton, John; Langleben, David; Kutryk, Michael B.; Camack, Nancy; Galipeau, Jacques; Courtman, David W.; Stewart, Duncan J.
<x xml:space="preserve">Abstract</x> Rationale: Pulmonary arterial hypertension (PAH) remains a progressive and eventually lethal disease characterized by increased pulmonary vascular resistance because of loss of functional lung microvasculature, primarily at the distal (intracinar) arteriolar level. Cell-based therapies offer the potential to repair and regenerate the lung microcirculation and have shown promise in preclinical evaluation in experimental models of PAH. Objective: The Pulmonary Hypertension and Angiogenic Cell Therapy (PHACeT) trial was a phase 1, dose-escalating clinical study of the tolerability of culture-derived endothelial progenitor cells, transiently transfected with endothelial nitric oxide synthase, in patients with PAH refractory to PAH-specific therapies. Methods and Results: Seven to 50 million endothelial nitric oxide synthase–transfected endothelial progenitor cells, divided into 3 doses on consecutive days, were delivered into the right atrium via a multiport pulmonary artery catheter during continuous hemodynamic monitoring in an intensive care unit setting. Seven patients (5 women) received treatment from December 2006 to March 2010. Cell infusion was well tolerated, with no evidence of short-term hemodynamic deterioration; rather, there was a trend toward improvement in total pulmonary resistance during the 3-day delivery period. However, there was 1 serious adverse event (death) which occurred immediately after discharge in a patient with severe, end stage disease. Although there were no sustained hemodynamic improvements at 3 months, 6-minute walk distance was significantly increased at 1, 3, and 6 months. Conclusion: Delivery of endothelial progenitor cells overexpressing endothelial nitric oxide synthase was tolerated hemodynamically in patients with PAH. Furthermore, there was evidence of short-term hemodynamic improvement, associated with long-term benefits in functional and quality of life assessments. However, future studies are needed to further establish the efficacy of this therapy. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00469027.